SPECT findings in Parkinson's disease associated with dementia. Issue 10 (October 1992) - Sawada, H; Udaka, F; Kameyama, M; Seriu, N; Nishinaka, K; Shindou, K; Kodama, M; Nishitani, N; Okumiya, K
Abstract : Dementia in Parkinson's disease is thought to be attributable not only to subcortical lesions but also to cortical alterations, especially frontal lobe dysfunction. To evaluate cortical function, the regional cerebral blood flow (rCBF) was estimated of 13 demented and 13 non-demented age matched patients with Parkinson's disease compared with that of 10 age matched controls using I-123 iodoamphetamine single photon emission tomography (IMP-SPECT). The rCBF of the nondemented Parkinson's patients showed no significant differences from that of the control subjects. In the demented patients, the bilateral frontal and parietal and left temporal regional blood flow was significantly less than in the controls. Four demented patients showed isolated frontal hypoperfusion, 8 showed fronto-parietal hypoperfusion, and 1 showed isolated parietal hypoperfusion. Frontal hypoperfusion was therefore present in 12 of the 13 demented patients, and this finding agrees with the frontal lobe dysfunction hypothesis. Parietal rCBF had a significant positive correlation with cortical functions such as calculation and language ability in the MMSE scores. The parietal and temporal reduction in rCBF probably reflects the presence of Alzheimer pathology, cortical Lewy body disease, or both.